THE INSTAGRAM SOCIAL MEDIA ACCOUNT @MAGI.SPACE IN PROMOTING A HEALTHY LIFESTYLE AMONG GENERATION Z - Firdausi Nur Aulia; RR Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The rapid development of digital technology and the increasing use of social media have transformed the way Generation Z obtains information and shapes their lifestyle, including the adoption of healthy living practices. Social media has evolved beyond an entertainment platform and now functions as a medium for education and community building that encourages awareness of physical and mental well-being. This study aims to analyze the role of the Instagram account @magi.space in promoting a healthy lifestyle among Generation Z and to explore audience responses and perceptions toward the content presented. This research employed a qualitative approach with a descriptive method. Data were collected through non-participant observation, in-depth interviews, documentation, and source and technique triangulation. The informants consisted of the account manager, Generation Z followers, and a triangulation informant. The findings indicate that @magi.space serves as a medium for promotion, education, interaction, and wellness community building through the use of Feeds, Reels, and Instagram Stories. The content is perceived as informative, engaging, and relevant to the needs of young audiences, encouraging motivation to adopt healthy lifestyles, expand social interactions, and increase awareness of physical and mental health. The novelty of this study lies in its examination of a community-based Instagram account in fostering Generation Z's awareness and interest in healthy living through the integration of digital content, community interaction, and participatory experiences.